The Interplay Between TGF-β Signaling and Cell Metabolism - Liu, Huidong; Chen, Ye-Guang (Frontiers in Cell and Developmental Biology, 2022)
The transforming growth factor-β (TGF-β) signaling plays a critical role in the development and tissue homeostasis in metazoans, and deregulation of TGF-β signaling leads to many pathological conditions. Mounting evidence suggests that TGF-β signaling can actively alter metabolism in diverse cell types. Furthermore, metabolic pathways, beyond simply regarded as biochemical reactions, are closely intertwined with signal transduction. Here, we discuss the role of TGF-β in glucose, lipid, amino acid, redox and polyamine metabolism with an emphasis on how TGF-β can act as a metabolic modulator and how metabolic changes can influence TGF-β signaling. We also describe how interplay between TGF-β signaling and cell metabolism regulates cellular homeostasis as well as the progression of multiple diseases, including cancer.